Anisotropic characteristics of mesoscale fractures and applications to wide azimuth 3D P-wave seismic data. (26th May 2015) - Wang, Yaojun; Chen, Shuangquan; Li, Xiang-Yang
Abstract: Mesoscale fractures of length on the order of centimeters to meters play a crucial role in fluid flow and hydrocarbon production in fractured reservoirs, and are of great interest to reservoir engineers. Therefore, we need to find a method for obtaining information on mesoscale fractures. Most information on fractures comes from seismic data, specifically through the study of fracture-induced azimuthal anisotropic attributes, such as velocity variation with azimuth (VVAZ), amplitude variation with azimuth (AVAZ) and Q (quality factor for attenuation) variation with azimuth (QVAZ). Using these anisotropic attributes to characterize fracture orientations and densities has been performed for a long time. However, it has not been reported whether these methods can be used to detect mesoscale fractures. In this study, through analysis of the anisotropic response to different lengths of fractures based on a mesoscale fracture model, we find that azimuthal anisotropic attenuation is only sensitive to mesoscale fractures, while the anisotropic velocity represents the response for overall scale fractures. Two models, containing mesoscale fractures of length 1 m and microscale fractures of length 0.01 m, are used to calculate synthetic seismograms. Through analysis of the azimuthal anisotropic attributes (VVAZ, AVAZ and QVAZ) from the synthetic seismograms, the identification ability for microscale and mesoscale fractures is compared. It is observed that QVAZ can be used to invert mesoscale fractures while VVAZ and AVAZ cannot. Finally, the QVAZ method is applied in a wide azimuth 3D P-wave seismic dataset to detect mesoscale fractures and the results are confirmed by imaging loggings. Thus, synthetic seismograms, rock physics analysis and field seismic application demonstrates that anisotropic attenuation is the most effective method to detect mesoscale fractures in wide azimuth 3D P-wave seismic data.